THE PREVALENCE OF OCCUPATIONAL INJURIES AND ILLNESSES IN ASEAN: COMPARISON BETWEEN INDONESIA AND THAILAND - Irfani, Tri Hari (Public Health of Indonesia, 2015)
Work is important in daily lives. ASEAN countries, especially in Indonesia and Thailand, the two countries are facing the era of improving industrial. The more increasing industry, the higher the level of accidents and diseases that will burden to the workers. In Indonesia, small industry is the biggest industry with a frequency of 83.70%. Accidents and illnesses to workers is still relatively high, eight workers died every day. In Thailand, 62.6% from 39.3 millions of workers, working as an informal and mostly in the agriculture sector. The number of workers who suffered accidents and diseases is also high, 129.632 in 2011 workers injured at work and accident and 37.933 of them were severe. Furthermore, due to the higher number of accident and diseases related with work in these two countries, it must take a more optimal prevention in order to reduce those problems.